HEATHCLIFF’S NEUROSIS IN BRONTЁ’S WUTHERING HEIGHTS NOVEL - Sari, Noor Laila; Kuncara, Singgih Daru; M., Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
This research was conducted to explore Heathcliff in Emily Brontë’s Wuthering Heights novel psychologically. The researcher was aimed to find out the factors which contributed to the development of Heathcliff’s neurosis and to reveal the neurotic trends that appear in Heathcliff as he attempts to fight against his conflicts. The researcher used qualitative method with content analysis approach in conducting this research. The researcher analyzed Heathcliff by applying the literary theory and psychological theory. The researcher found that the main cause of Heathcliff’s neurosis as portrayed in Wuthering Heights novel was basic anxiety produced by the social environment where he lived. The factors that contributed to his development of neurosis were familial interference and the Victorian culture based on competition. Consequently, he developed three (3) neurotic trends as his defense mechanism to fight against his conflicts. These neurotic trends were (1) moving toward people; (2) moving against people; and (3) moving away from people.